EPISTOLARY INTERCOURSE AS A PHILOSOPHICAL GENRE: ANALYSIS IN THE CONTEXT OF H.S. SKOVORODA’S HERITAGE - Sukhodub, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The subject of this article is the philosophical heritage of H.S. Skovorodа. The author examines the philosophical and anthropological problems posed by the thinker on the basis of his correspondence with students and friends. The aim of the study is to analyze the philosophical problems of the epistolary heritage of H.S. Skovorodа. The tasks are to reveal the thematic content of the problems of man and the «man’s world» that are posed in the letters of the philosopher; to analyze the form and basic principles of such a specific text of philosophical reasoning as letters. The core of the research methodology is based on a systematic approach. Thinking as interpretation as a principle of hermeneutics is also applied in the study. Research results. Analysis of the epistolary heritage of H.S. Skovoroda made it possible to holistically present the creativity of the philosopher. Textual analysis of the correspondence allowed us to assert that Skovoroda’s letters represent a special genre of philosophical reflections. The letters reveal the philosopher’s doctrine of man as a «small world», his understanding of the conditions of human happiness, the idea of self-knowledge, etc. Discussion. Scientific interest was the work of contemporary authors, which considered the creative heritage of the thinker in the aspects of philosophical anthropology and the philosophy of dialogue (V. Bodak, V. Wozniak, S. Wozniak, M. Galushchak, V. Limonchenko, A.-L. Maftiy, G. Pankov, J. Yanko). Conclusion. The letters of H.S. Skovorodа to his students and friends revealed the dialogical nature of the thinking of a philosopher. An analysis of the content of the letters shows that they contain not only the mentorship of a teacher, which is characteristic communication between teacher and student, but also the development of the philosopher’s teaching about man, as well as a rethinking of one’s own life path. The analysis of the text of the letters shows that the philosopher professes the principle of the unity of education and upbringing of the younger generation, which is revealed as the «law» of philosophical and educational activities.